The shape of sound: rendering interactive six-degrees-of-freedom audio in software - Rehberg, Daniel, author; Ortega, Francisco Raul, advisor; Rajopadhye, Sanjay, committee member; Malinin, Laura, committee member (Colorado State University. Libraries, 2024)
Six-degrees-of-freedom (6DoF) audio is an area of growing interest in interactive software, but it has faced several challenges: it does not easily conform to object-based rendering when achieved with arrays of ambisonics microphones; prior studies rely on subjective metrics which do not clearly indicate how this additional audio interaction might aid a human in a localization task (an indication of enhanced spatial awareness of a sound event); and the ambisonics technique requires specialized equipment and recording space, as well as audio engineering expertise for setup and calibration to work properly. These factors limit the accessibility of 6DoF audio to be implemented in research experiments or within commercial products like videogames. My work has involved taking an interdisciplinary approach to design, prototype, and validate (with human subjects) an inherently object-based 6DoF rendering method. This method exploits computational geometry techniques and follows a rendering paradigm inspired by the programmable graphics pipeline to create 3D audio meshes which can be transformed in real time to dynamically render monaural audio samples – meaning the output of the method can still be input into contemporary audio filtering and spatialization functions/tools, like a head-related transfer function. This work includes two studies performed with human subjects as well as a breakdown of the rendering method and its prototype implementation. The results of the human-subject studies indicate clear advantages to localizing a spatial sound in 3D space compared to the contemporary three-degrees-of-freedom approach.
Keywords: 6DoF audio; interactive software; spatialized sound; audio rendering; 3D audio; simulation